Let's solve each equation step by step:
-
For the equation \(2x - 6 = 24\): \[ 2x - 6 = 24 \ 2x = 24 + 6 \ 2x = 30 \ x = \frac{30}{2} \ x = 15 \]
-
For the equation \(2x + 6 = 24\): \[ 2x + 6 = 24 \ 2x = 24 - 6 \ 2x = 18 \ x = \frac{18}{2} \ x = 9 \]
-
For the equation \(2(x + 6) = 24\): \[ 2(x + 6) = 24 \ x + 6 = \frac{24}{2} \ x + 6 = 12 \ x = 12 - 6 \ x = 6 \]
-
For the equation \(2(x - 6) = 24\): \[ 2(x - 6) = 24 \ x - 6 = \frac{24}{2} \ x - 6 = 12 \ x = 12 + 6 \ x = 18 \]
Now we have the solutions for each equation:
- \(2x - 6 = 24\) → \(x = 15\)
- \(2x + 6 = 24\) → \(x = 9\)
- \(2(x + 6) = 24\) → \(x = 6\)
- \(2(x - 6) = 24\) → \(x = 18\)
Now we can match the solutions with the correct equations:
- 15 matches with \(2x - 6 = 24\)
- 9 matches with \(2x + 6 = 24\)
- 6 matches with \(2(x + 6) = 24\)
- 18 matches with \(2(x - 6) = 24\)
Responses:
- 15: \(2x - 6 = 24\)
- 9: \(2x + 6 = 24\)
- 6: \(2(x + 6) = 24\)
- 18: \(2(x - 6) = 24\)